Clinical and genetic risk factors define two risk groups of extracranial malignant rhabdoid tumours (eMRT/RTK). (January 2021) - Nemes, Karolina; Bens, Susanne; Kachanov, Denis; Teleshova, Margarita; Hauser, Peter; Simon, Thorsten; Tippelt, Stephan; Woessmann, Wilhelm; Beck, Olaf; Flotho, Christian; Grigull, Lorenz; Driever, Pablo H.; et al.
Abstract: Introduction: Extracranial rhabdoid tumours are rare, highly aggressive malignancies primarily affecting young children. The EU-RHAB registry was initiated in 2009 to prospectively collect data of rhabdoid tumour patients treated according to the EU-RHAB therapeutic framework. Methods: We evaluated 100 patients recruited within EU-RHAB (2009–2018). Tumours and matching blood samples were examined for SMARCB1 mutations by sequencing and cytogenetics. Results: A total of 70 patients presented with extracranial, extrarenal tumours (eMRT) and 30 with renal rhabdoid tumours (RTK). Nine patients demonstrated synchronous tumours. Distant metastases at diagnosis (M+) were present in 35% (35/100), localised disease (M0) with (LN+) and without (LN−) loco-regional lymph node involvement in 65% (65/100). SMARCB1 germline mutations (GLM) were detected in 21% (17/81 evaluable) of patients. The 5-year overall survival (OS) and event-free survival (EFS) rates were 45.8 ± 5.4% and 35.2 ± 5.1%, respectively. On univariate analyses, age at diagnosis (≥12 months), M0-stage, absence of synchronous tumours, absence of a GLM, gross total resection (GTR), radiotherapy and achieving a CR were significantly associated with favourable outcomes. In an adjusted multivariate model presence of a GLM, M+ and lack of a GTR were the strongest significant negative predictors of outcome. Conclusions: We suggest to stratify patients with localised disease (M0), GTR+ and without proof of a GLM (5-year OS 72.2 ± 9.9%) as 'standard risk'. Patients presenting with one of the features M+ and/or GTR− and/or GLM+ belong to a high risk group (5-year, OS 32.5 ± 6.2%). These patients need novel therapeutic strategies such as combinations of targeted agents with conventional chemotherapy or novel experimental approaches ideally within international phase I/II trials. Highlights: Presence of GLM, M+ and lack of GTR are significant negative prognostic factors. A Standard risk' (SR) group contains patients with M0 and GTR+ and without GLM. A 'High risk' (HR) group presents patients with M+ and/or lack of GTR and/or GLM. The SR group demonstrated significantly superior 5-year OS rates (72.2%). SR patients benefit from standard conventional chemotherapy, HR patients need novel therapeutic strategies.